2008
DOI: 10.1002/ijc.23799
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling identifies an interferon‐associated host immune response in invasive squamous cell carcinoma of the skin

Abstract: Squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) represent the 2 most common types of nonmelanoma skin cancer. Both derive from keratinocytes but show a distinct biological behavior. Here we present transcriptional profiling data of a large cohort of tumor patients (SCC, n 5 42; BCC, n 5 114). Differentially expressed genes reflect known features of SCC and BCC including the typical cytokeratin pattern as well as upregulation of characteristic cell proliferation genes. Additionally, we found increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…This finding is supported by the findings that it is downregulated in gastric [47] and recurrent breast cancers [48]. However, IRF1 may not always act as a tumor-suppressor, as there is a report that it is upregulated in skin squamous cell carcinoma [49]. Therefore, our observation of upregulated IRF1 in NSCLC samples requires further attention to explore the precise role of this TF in various cancers.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is supported by the findings that it is downregulated in gastric [47] and recurrent breast cancers [48]. However, IRF1 may not always act as a tumor-suppressor, as there is a report that it is upregulated in skin squamous cell carcinoma [49]. Therefore, our observation of upregulated IRF1 in NSCLC samples requires further attention to explore the precise role of this TF in various cancers.…”
Section: Discussionsupporting
confidence: 81%
“…IFI27 is suggested to be involved in proliferation of skin keratinocytes [29] and up-regulated in breast cancer, SCC of the skin and ovarian cancer [3032]. In ovarian cancer IFI27 is associated with patient survival where high IFI27 expression correlates with poor disease free survival [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed a significant increase in the expression of five genes with overlapping functions in antigen presentation and osteoclastogenesis in the good responder group – IFI30 ( P =0.0005), TYROBP/DAP12 ( P =0.002), TMSB10 ( P =0.003), CTSB ( P =0.004), and SPP1 ( P =0.037). The IFI30 expression, in melanoma (Goldstein et al , 2008) and squamous cell carcinoma (Wenzel et al , 2008), has been shown to enhance antigen presentation and to activate CTSB (Goldstein et al , 2008), which is required for osteoclast fusion during differentiation (McMichael et al , 2009). In addition, TYROBP/DAP12 is associated with active innate immune responses (Lanier, 2009) and, together with SPP1, also has a crucial function in osteoclast differentiation (Humphrey et al , 2004; Mocsai et al , 2004; Dalla-Torre et al , 2006; Inui et al , 2009).…”
Section: Discussionmentioning
confidence: 99%